A Cognitive Science Analysis of the Quaker Business Method: Is How It Works Why It Works?. Issue 2 (December 2019) - Cheng, Peter C.-H.
Abstract : The Quaker Business Method (QBM) has been in development for over 300 years. Quakers believe that the QBM is an effective means for making decisions. This paper develops a tripartite theoretical framework to analyse the QBM in order to examine its efficacy, in terms of both the quality of its processes and the morality of its decisions. The framework encompasses: (1) a decomposition of the QBM as a set of tools; (2) a selection of theories and models from Cognitive Science that explain how humans think; (3) a set of relational models that can be used to objectively judge the morality of different forms of human behavioural interactions. Overall, it appears that QBM tools may counter the deficits in natural human abilities to reason and solve problems, that they may promote decision-making practices that are moral and that the resulting decisions, themselves, may be moral.